The evolution of the medieval world society, government and thought in Europe, 312 - 1500 - Nicholas, David (Longman, 1992)
"Although David Nicholas considers political ideas, he is more concerned to explore the realities of public administration and the mechanics of government in medieval Europe, at all levels - local, regional, national. While most medieval textbooks emphasise clerical culture at the expense of lay, Professor Nicholas offers a more balanced approach, with sections on lay and vernacular culture for the early Middle Ages as well as the later. Similarly, he sees education not simply as an extension of religion, but also as a carefully-structured curriculum with practical applications in the workplace. Religion itself is treated as a concern of the laity as well as of the clergy, and there are accordingly substantial sections on folk religion. And Professor Nicholas's research interests in the history of women, children and the family in the Middle Ages are also richly reflected throughout his text." "In less expert hands, the book's huge chronological and geographical spread could well have become unwieldy; but David Nicholas seizes the unique opportunity of his vast canvas to explore the major themes of the age in depth and in time. His pages never become superficial or simplistic; nor, for all the wealth of information they convey, is their richness of detail ever allowed to overwhelm the clear and vigorous lines of the argument. This is a scholarly book that the student and general reader can enjoy. It is a notable achievement."--BOOK JACKET